Spray-drying of xylanases produced by Myceliophthora thermophila under solid-state cultivation - Delmaschio, I. B. [UNESP]; Garcia, R. L. [UNESP]; Gomes, E. [UNESP]; Thoméo, J. C. [UNESP] (Springer Nature, 2024)
Production xylanases at low cost and their storage stability are of utmost importance for the animal feed industry. This work aimed to produce fungal xylanases by solid-state cultivation and to immobilize the enzymes in agricultural residues by spray-drying. The enzymes were obtained by cultivating Myceliophthora thermophila I-1D3b in sugarcane bagasse and wheat bran at 45 °C and 75% moisture content (w.b.) and the titres were as high as 864 U per gram of dry solids. The physical–chemical activity of the enzyme showed to be of interest for the animal feed industry, as the optimal activity was obtained at pH 5.0 and the optimal temperature at 70 °C. The enzymes were spray-dried using soybean meal, wheat bran, and corn bran as carriers, and the most suitable carrier was soybean meal in terms of residual enzyme activity after drying. The operational conditions for soybean meal were optimized, with the outlet temperature, the liquid flow rate, and the total solid content as variables, and only the total solid content was significant. The highest residual enzyme activity was 130.9% after optimization. Experiments for storage of the dry powders of soybean meal showed that the loss of activity was under 30% for storage times up to 45 days. The results here presented are promising for the reduction of costs of xylanases used as feed enzymes and for their preservation for long periods as a dry powder.
Keywords: Animal feed; Solid-state cultivation; Spray-drying; Storage; Xylanases